Ichthyo-diversity assessment of the Old Brahmaputra river, Bangladesh: present stance and way forward. Issue 11 (November 2020) - Bashar, Abul; Rohani, Md. Fazle; Uddin, Md. Rois; Hossain, Md. Sazzad
Abstract: The study was carried out to obtain information on the present status and trend of finfish diversity of the Old Brahmaputra river, Bangladesh. Samples were collected directly from a professional fishing boat caught by different nets, traps and hooks from January 2019 to December 2019. Together with 4 exotic species, a total of 49 species under 6 families were recorded. Though a biodiversity index of 3.65854 and a dominance index of 0.030929 represent the richness of ichthyo-diversity within the river, Synbranchiformes and Tetraodontiformes were not reported throughout the study period. Linear regression analysis showed a positive correlation between water height of the river and monthly abundance of the species found. Catch composition of catfishes and snakeheads slumped while barbs showed triumph over previous findings. A majority of fish recorded were within the least concern category according to IUCN (2015) but portions also belonged to critically endangered, endangered, and vulnerable categories as well. Therefore, conservation measures must be infixed in the Old Brahmaputra river to hold the fish diversity in a sustainable state. Abstract : Fish Diversity; The Old Brahmaputra river; Shannon Index; Simpson Index; Agricultural Science; Animal Science; Aquaculture; Biodiversity; Fishery Management